2019
DOI: 10.1111/iji.12470
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytotoxic T‐lymphocyte associated protein 4 gene polymorphisms with the risk and prognosis of oesophageal cancer in a high‐incidence region from northern China

Abstract: The most important anti‐tumour immune response is mediated by T lymphocytes. Cytotoxic T lymphocyte‐associated protein 4 (CTLA4) plays a critical role in the immune surveillance against tumours as an inhibitory immune checkpoint molecule of T‐cell activation. This study was designed to explore the association of CTLA4 polymorphisms with the susceptibility to oesophageal squamous cell carcinoma (ESCC) and prognosis of patients with ESCC in a high‐incidence population from northern China. CTLA4 rs5742909 C/T and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
7
2
Order By: Relevance
“…Previously, there have been many reports about the association between rs5742909 C/T and cancer risk, but the results were still controversial. The meta‐analysis suggested that the T allele of rs5742909 C/T might increase an individual's susceptibility to gastric cancer, cervical cancer, and leukemia, 19–21 but it may not be related to the risk of esophageal cancer, lymphoid malignancy, and breast cancer 16,22,23 . However, the results show that the frequency of the T allele of rs5742909 C/T in epithelial ovarian cancer patients is significantly lower than that in the control group in the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Previously, there have been many reports about the association between rs5742909 C/T and cancer risk, but the results were still controversial. The meta‐analysis suggested that the T allele of rs5742909 C/T might increase an individual's susceptibility to gastric cancer, cervical cancer, and leukemia, 19–21 but it may not be related to the risk of esophageal cancer, lymphoid malignancy, and breast cancer 16,22,23 . However, the results show that the frequency of the T allele of rs5742909 C/T in epithelial ovarian cancer patients is significantly lower than that in the control group in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…The metaanalysis suggested that the T allele of rs5742909 C/T might increase an individual's susceptibility to gastric cancer, cervical cancer, and leukemia, [19][20][21] but it may not be related to the risk of esophageal cancer, lymphoid malignancy, and breast cancer. 16,22,23 However, the results show that the frequency of the T allele of rs5742909 C/T in epithelial ovarian cancer patients is significantly lower than that in the control group in the present study. Women carrying the T allele may have a lower risk of developing epithelial ovarian cancer than those with the C allele.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In the PPI network of 68 DEGs, we found that some immune response genes are at the relative core of the PPI network, such as CD86, LCP2, TLR7, CSF1R, C1QA, IRF8, CTLA4 and so on. Among them, TLR7 has been reported to be overexpressed in ESCC [23] , and CTLA4 is related to the poor prognosis of patients with ESCC [24] . Finally, we searched the genes related to the risk and prognosis of ESCC from the CCGD-ESCC database.…”
Section: Discussionmentioning
confidence: 99%